Age and growth, reproduction and diet of the red blenny Parablennius ruber (Blenniidae) - Azevedo, José M. N. (2002)
Basic biological information for a sublittoral population of the red blenny Parablennius ruber is presented based on a two-year study involving 2350 specimens. The length-weight relationship was given by TW = 0.011 x TL2.963 (where TW = total weight, in g; TL = total length, in cm). Age at length data was inferred by modal analysis of the monthly length-frequency distributions. The parameters of the fitted von Bertalanffy growth equation (with seasonal component, birth date on February, 15th) were L∞ = 13.22 cm; K = 0.62 year-1; to = -0.39 year; C = 0.68; WP = 0.97. Macroscopic examination of the gonads, and analysis of the monthly values of the gonadosomatic index, indicated that reproduction occurs in winter, with a maximum in February and March, when water temperatures are low. Individuals become sexually mature around 6 cm TL, a size that can be reached in less than one year. Stomach contents suggest an omnivorous diet mainly composed of scrapped filamentous algae and associated invertebrates.